Olympic Social Values and Yoga: An Examination of Physical Educators' and Students' Perceptions - Bhadauria, Sadhvi (Πανεπιστήμιο Πελοποννήσου, 2025)
This researched examined the perceptions of Physical Education teachers and students regarding the incorporation of social values through the practice of yoga. This study aims to explores the perceptions of Physical Education teachers and students regarding the role of yoga in teaching Olympic values like cooperation, respect, responsibility, honesty, empathy, kindness, and self-control. Understanding these views is important to see if yoga effectively supports students' overall growth. Specific objectives were set for this study, the objectives of the present study could be summarized as follows: to find out physical educators' perceptions concerning their preparedness to integrate and teach social values in their yoga lessons. To assess the impact of yoga on students' behaviour from the perspective of the PE teachers. To evaluate students' perceptions of the social values they learn from yoga, examining both how these values may impact their behaviour and whether students view them as beneficial for personal growth and character development. The study employed quantitative research by distributing questionnaires via Google Forms to understand the integration of values in yoga sessions, changes in students’ behaviour, and the overall impact of yoga sessions in school settings in Delhi NCR, India. The findings highlighted that both PE teachers and students perceived yoga to have a positive impact on student’s behaviour. Both groups recognized the significant influence of practicing yoga and learning and implementing values on themselves, their surroundings, and their daily lives. They agreed that yoga helps students become better individuals, promotes self-awareness, and encourages personal change. The study concludes that the social values taught through yoga have a profoundly positive and effective impact on student’s behaviour and life skills. Practicing yoga had a positive impact on students' mental, physical, and psychological health. They learned social values that made them better individuals, helping them control their anxiety, emotions, and stress while contributing to their overall development. It was found that the social values taught through yoga promote the Olympic values. Therefore, it is recommended that yoga serve as a valuable tool in the Olympic Values Education Programme to create a more effective and greater impact on children’s holistic development across the globe.
Keywords: Φυσική αγωγή για παιδιά - Ινδία; Φυσική αγωγή και εκπαίδευση - Ινδία; Καθηγητές φυσικής αγωγής - Στάσεις - Ινδία; Γιόγκα - Θεραπευτική χρήση; Ολυμπιακές αξίες; Physical education for children- India; Physical education and training - India; Physical education teachers - Attitudes - India; Yoga - Therapeutic use; Olympic values; Yoga Olympic; Olympic Values; Education; Physical Education Teachers; Social Values; India; Children; Student